Endoscopic Fasciotomy of the Superficial and Deep Posterior Compartments of the Leg - Tun Hing Lui, M.B.B.S.(H.K.), F.R.C.S.(Edin.), F.H.K.A.M., F.H.K.C.O.S. (Arthroscopy Techniques, 2017)
Chronic exertional compartment syndrome is a rare cause of lower leg pain incurred during sports activities and typically affects young athletes who need to return to their activity level as quickly as possible. Nonoperative treatments are often unsuccessful and fasciotomy of the involved compartment is the treatment of choice. Endoscopically assisted release of the anterior and deep compartments is proven to be safe and effective. Endoscopically assisted deep posterior compartment release via an incision 1 to 3 cm behind the medial tibial border has high risk of injury to the great saphenous and perforating veins and the saphenous nerve. The purpose of this Technical Note is to describe the details of endoscopic fasciotomy of the superficial and deep posterior compartments of the leg. The operative field of this approach is away from the saphenous vein and nerve. Moreover, the tibial insertion of the soleus muscle does not need to be released to gain access to the proximal part of the deep posterior compartment.